Healthcare interoperability through intelligent agent technology - Cardoso, Luciana (2014)
With technological advances, the amount of data and the information systems in healthcare units has been increasing exponentially. The accessibility and availability of patients’ clinical information are a constant need. The Agency for Integration, Diffusion and Archive of Medical Information (AIDA) was developed to fulfill this need and it was implemented at the Centro Hospitalar do Porto (CHP), revealing a highly successful, ensuring interoperability among CHP healthcare information systems. This paper presents a new AIDA module, which aims to monitor the activity of its agents. It revealed its usefulness, providing to the user the functionalities and the necessary data for it to make a complete monitoring of the activities of each AIDA agent. It was still considered an efficient system, since it does not compromise the resources of the machine where it was implemented. In addition, this module increases AIDA functionality and efficiency.